GST and the Effects on Pharmaceutical Industry: Unraveling the Impact of GST on India's Pharmaceutical Industry (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The pharmaceutical industry has been one of the engines of growth for India. In recent times, despite cost pressures and unfavorable macroeconomics, the industry has continued to show signs of growth. The introduction of Goods and Services Tax (GST) has certainly had an impact on pharmaceutical services. In this paper, RSM explores at a broad level, the impact that GST has had on the pharmaceutical industry. We believe that understanding and identifying these issues is important and industry must appreciate that GST as a law has not fully evolved.